Self-Care Needs in Patients with Physical Immobilization - Novia Shinthia Dewie; Eka Misbahatul Mar'ah Has (Jurnal Ners, 2017)
Introduction: The quantity of unfulfilment of self-care in patients with physical immobilisation can decrease the quality indicator of nursing care. Self-care for physically immobilised patients is affected by basic condition factors. The study aimed to analyse the factors that can affect the fulfilment of self-care needs in patients with physical immobilisation.Methods: The study design was descriptive cross-sectional, with purposive sampling technique and the samples were 36 nurses and 36 physically immobilised patients. The independent variable was the fulfilment of self-care needs. Dependent variables were patient demography (age, sex), nurse (knowledge, action, motivation), and health care factors (occupation design/nursing care method). The instrument used was a questionnaire and observation form. Data were then analysed using double linear regression analysis, with significance ɑ ≤ 0.05.Results: From the double linear regression test result was obtained p-value (Sig) = 0.000 R Square = 0.889. Partially it was obtained p-value of age p(sig)=0,005, sex p(Sig)=0.038, knowledge p(Sig)=0.889, action p(Sig)= 0.000, and motivation p(Sig)=0.003.Conclusion: Factors of patients (age, sex) and nurses (action, motivation) influence the fulfilment of self-care needs for patients with physical immobilisation. However, nurses’ knowledge does not have any influence. The study result can be considered as input for nurses in developing the quality of nursing care in the fulfilment of self-care needs.